Assessment of satellite-based MERRA climate data in AASHTOWare pavement mechanistic-empirical design. Issue 12 (2nd December 2022) - Gopisetti, Praveen; Ceylan, Halil; Cetin, Bora; Kim, Sunghwan
Abstract : The pavement performance system depends on various factors including traffic loading, climate conditions, and material properties. Variations in ambient temperatures and moistures can change material properties and consequently affect the overall pavement performance. Collecting climate data has been a significant challenge. This study compares the pavement performance predictions of Iowa composite pavement systems in AASHTOWare Pavement ME Design (PMED) software using four climate data sources: (1) ground-based weather station, (2) North American Regional Reanalysis and (3) the Modern-Era Retrospective Analysis for Research and Applications (MERRA) version 1 and (4) MERRA version 2. The findings showed disagreement among climate data sources for some of the distresses due to the significant differences in percent sunshine hourly measurements. Database for 'synthetic' percent sunshine is developed using surface shortwave radiation (SSR) estimates directly provided by MERRA to improve pavement performance predictions. This study recommends the use of SSR as an input in PMED.